2018
DOI: 10.17265/2161-6256/2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pest Exclusion Net (PEN) on the Sustainable Production of Late Season Broad Leaf Mustard (BLM) in Chitwan, Nepal

Abstract: Broad leaf mustard (BLM) (Brassica juncea L. var. rugosa, Brassicaceae) is one of the most widely consumed vegetable crops in Nepal. The production of crop in open field is constrained by major pests like mustard aphid and flea beetle. This study was aimed to determine the effects of pest exclusion net (PEN) on pest-infestation and yield of BLM cultivar "Khumal Broad Leaf". The experiment was carried out in randomized complete block design (RCBD) with five treatments and four replications. The treatments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This vegetative parameter was superior in reflective mulch compared to black plastic mulch as reflective mulch has repellent characteristics against aphid and other small insects. Neupane et al (2018) also reported the highest yield attributing characteristics in broadleaf mustard inside net house + black plastic mulch followed by black plastic mulch + imidacloprid spray, reflective mulch and black plastic mulch.…”
Section: Effects Of Different Mulching and Net House On Yield And Yiementioning
confidence: 93%
See 1 more Smart Citation
“…This vegetative parameter was superior in reflective mulch compared to black plastic mulch as reflective mulch has repellent characteristics against aphid and other small insects. Neupane et al (2018) also reported the highest yield attributing characteristics in broadleaf mustard inside net house + black plastic mulch followed by black plastic mulch + imidacloprid spray, reflective mulch and black plastic mulch.…”
Section: Effects Of Different Mulching and Net House On Yield And Yiementioning
confidence: 93%
“…The problem associated with pesticide use can be overcome by growing crops in a protected environment such as net house and use of mulching materials. Growing crops inside the net house (Neupane et al, 2018;Bhusal et al, 2019) and use of mulching (Orozco-Santos et al, 1995) lower insect pest population and increase yield. Therefore, this study was carried out to evaluate the efficacy of different mulching materials and net house against crucifer aphid of broadleaf mustard during the winter season in Chitwan, Nepal.…”
Section: Introductionmentioning
confidence: 99%